Dikes and Society in Rural China: The Jianghan Plain, 1788-2010s - Zhang, Jiayan, (Social Sciences E-Books Online, Collection 2026., 2025)
To feed an ever-growing population in a water-rich region, the people of the Jianghan Plain in Central China constantly built dikes and polders. As China's political system changed dramatically from 1788 to the 2010s, the governance of Jianghan's dikes and polders also changed, moving from indirect supervision by the state to direct management. This shift has dramatically improved the security of the dike systems and has had a profound impact on the Jianghan people's lives. Based on rarely used local gazetteers and newly available archival materials, this book uses a multidimensional interactive approach to explore water control and state-society relations in rural China over the past three centuries.